2020
DOI: 10.1097/pq9.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Medical Emergency Team Calls at a Tertiary Care Children’s Hospital

Abstract: Introduction: Medical emergency teams (METs) bring critical care expertise to the bedsides of hospital ward patients who may be deteriorating. Diurnal variation in MET activation rates may identify inconsistencies in the detection of patients needing intervention. We aimed to determine whether such variation exists at our tertiary care children’s hospital. Methods: In this retrospective cohort study, we collected data including date and time of MET and disposition following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This suggests that health care providers may be missing a critical period of patient deterioration overnight and delaying essential critical care interventions. 29 Consistent with other studies, we found that CDEs most frequently occurred in patients needing respiratory support, specifically, NIV across all time periods. 6 Of interest, our reported rates of invasive mechanical ventilation during CDEs are lower than previous studies, which is likely due to widespread use of NIV at our institution.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This suggests that health care providers may be missing a critical period of patient deterioration overnight and delaying essential critical care interventions. 29 Consistent with other studies, we found that CDEs most frequently occurred in patients needing respiratory support, specifically, NIV across all time periods. 6 Of interest, our reported rates of invasive mechanical ventilation during CDEs are lower than previous studies, which is likely due to widespread use of NIV at our institution.…”
Section: Discussionsupporting
confidence: 92%
“…We report a higher rate of unplanned PICU admission following daytime MET activation and a significant increase in the likelihood of unplanned PICU admission at 08:00, immediately following the period of lowest MET dosage overnight (00:00–07:59). 20 29 30 31 Our results suggest that important clinical deterioration may go undetected overnight in hospitalized pediatric patients leading to sicker patients by morning and consequently higher likelihood of unplanned PICU admission in the daytime. This may occur for several reasons.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations